A Cronbach's Alpha Generalization Meta-Analysis Study of the Problematic Pornography Consumption Scale. - Demirgül, Süleyman Agah; Sancar, Iskender Volkan; Demetrovics, Zsolt; Bőthe, Beáta (Sexual Health & Compulsivity)
The Problematic Pornography Consumption Scale (PPCS) was developed to assess problematic pornography use (PPU). A Cronbach's alpha generalization meta-analysis was conducted to estimate the average Cronbach's alpha score of the PPCS.Seventeen Cronbach's alpha scores from 12 studies (N = 41974) yielded excellent Cronbach's alpha score estimates. The average Cronbach's alpha score of the PPCS was.91 indicating excelltent internal consistency (95% CI =.883,.931; p <.001). Clinicians and researchers can be more confident in knowing that the PPCS is a reliable scale for measuring problematic pornography use across different populations.